Strategies for Low-Income Families in Facilitating Children to Learn Online During the Covid-19 Pandemic - Yolandari, Joesa; Fatmariza; Azwar Ananda; Yurni Suasti (MIMBAR PGSD Undiksha, 2023)
The existence of a policy for implementing online learning has an impact on many parents who cannot meet their children's learning needs due to financial constraints. This study aims to find out the efforts made by low-income families to overcome children's learning problems. This research belongs to the type of qualitative descriptive research, with research subjects,  13 low-income families, six children from low-income families, and one cooperative employee/neighbor who lent money. Data collection in this study was carried out using observation, interview, and documentation methods, with research instruments in the form of observation and interview guidelines. The data obtained in the study were then analyzed using data triangulation techniques which consisted of data reduction, data display, and conclusion or verification processes. The results of data analysis then show that low-income families make five efforts to meet the learning needs of children, including doing side jobs with a total percentage of 69%, utilizing the labor of other family members to supplement income with a total percentage of 54%, making savings with a total percentage of 93%, borrowing money from cooperatives or relatives with a total percentage of 85%, and utilizing assistance provided by the government with a total percentage of 100%. These results show that parents always try to provide learning facilities/infrastructure during the Covid-19 pandemic.